Pedagogical Practices and Psychological Influences on the Development of English-Speaking Skills in University Learners - Romero-Argueta, Jesús (Darul Yasin Al Sys, 2025)
This study examines the combined influence of pedagogical practices and psychological factors on the development of English speaking skills among university students in El Salvador. Persistent challenges in oral proficiency were addressed through a quantitative, correlational research design, using a Likert-scale questionnaire administered to 32 students at a private university. Statistical analysis revealed a strong positive correlation (r = 0.888, p < 0.001) between speaking skill development and the interaction of communicative teaching methodologies with psychological factors such as anxiety, confidence, and fear. The findings indicate that interactive approaches, including flipped classrooms and activity-based learning, together with supportive environments that reduce emotional barriers, significantly enhance students’ oral performance. The study highlights the importance of teacher training and curriculum design that combine methodological innovation with psychological support, ensuring more effective language acquisition. These results contribute to the improvement of English language education by offering evidence-based recommendations to strengthen speaking proficiency in EFL contexts similar to El Salvador.